Socio-economic and demographic factors associated with never having tested for HIV among sexually active men across the four administrative regions of Uganda - Otim Jude; Otim Nelson; Igeme Katagwa (BMC, 2021)
Abstract Background HIV testing among men is paramount in the prevention, diagnosis, and treatment of HIV. There is limited literature in understanding the socio-economic and demographic factors associated with never having tested for HIV among sexually active men aged 15 - 54 across the four administrative regions of Uganda. The purpose of this study is to investigate the socio-economic and demographic factors associated with never having tested for HIV among sexually active men aged 15 - 54 across the four administrative regions in the country. Methods The study used a cross-sectional research design to examine factors associated with never having tested for HIV among 4,168 sexually active men (15 - 54 years) across four administrative regions of Uganda using data from 2016 Uganda Demographic and Health Survey (UDHS). Frequency distributions, Pearson chi-square tests, and multivariable logistic regression were used to establish the association between never having tested for HIV among sexually active men (15 - 54 years) and selected independent variables across regions. Results About 20% of sexually active men (15 - 54 years) never tested for HIV across regions of the country. The major correlates amidst variability of never testing for HIV among sexually active men across regions were; educational level and marital status. Age, religious status, wealth quintile, worked in the last 12 months, circumcised, and one sexual partner in the last 12 months were only correlates of never having tested for HIV among respondents in particular regions of the country. Conclusion Findings in the study suggest promotion of male education, and suggest further investigation into the relationship between HIV non-testing among sexually active men (15 - 54 years) and being married across regions of the country. The study also proposes appreciation of regional differences in the outcome of HIV non-testing and suggests that efforts be focused on addressing regional differences in order to attain high HIV testing among sexually active men (15 - 54 years) across regions of Uganda, and thus reduce HIV related morbidity and mortality.